A influência do ambiente escolar e do letramento em cultura africana na crença de autoeficácia docente para o ensino dos objetos de conhecimento de matriz africana nas aulas de educação física - Alvares, Luis Eduardo (2025)
Despite the mandatory teaching of African culture according to Law 10.639/03, its presence in Brazilian schools is still limited and faces several challenges, such as prejudice and stereotypes, isolated practices on specific dates to meet protocols, and teachers' insufficient undergraduate education on this topic. In this context, it becomes relevant to investigate teachers' self-efficacy beliefs regarding the teaching of these contents. Teacher self-efficacy is defined as the judgment that teachers make about their ability to establish teaching strategies, create effective learning environments, and engage students even in the face of difficulties. Thus, teachers' confidence in their ability to teach African culture can directly influence their practices with this content in the school routine. This study aimed to investigate the relationship between teachers' perceptions of the influence of the school environment, their literacy in African culture, and their self-efficacy beliefs to teach this content in physical education classes. The study was exploratory and used a quali-quantitative approach. A questionnaire with a 0-10 scale was applied to assess teachers' perceptions of the influence of the school environment, literacy in African culture, and self-efficacy beliefs. For the study, the essential knowledge required for teaching African culture in physical education classes was defined, taking into account the legal framework, curriculum guidelines, and official documents in Brazilian education. Based on this knowledge, the specific domains for teaching African culture were identified, analyzing the diversity of content and knowledge dimensions (conceptual, procedural, and attitudinal). The results indicated that, although teachers reported a high perception of self-efficacy in topics such as combating racism and African-based games and play, this perception did not extend to topics such as African history and culture, African martial arts, and dances. Additionally, the findings showed that the higher the perception of literacy, the more favorable the school environment was perceived to be for teaching African culture, and the greater the self-efficacy in teaching this content. It was also found that internal factors related to personal moral agency tend to be more effective motivators than external regulators such as laws, curriculum guidelines, and official documents. Based on the results, the study highlights the need for racial and cultural literacy in teacher education to promote a more meaningful approach to this theme within the school curriculum, thereby enhancing self-efficacy beliefs for teaching this content in physical education classes.